ECB can lower fuel and heating costs by increasing interest rates but would risk economic recovery - Gökhan Ider; Alexander Kriwoluzky; Frederik Kurcz (DIW Weekly Report, 2022)
Inflation has been growing considerably since the middle of 2021, with rising energy prices driving the increase in particular. Since the end of February 2022, the trend has also been exacerbated by the ongoing Russian invasion of Ukraine. To keep prices stable, the European Central Bank must rein in its accommodative monetary policy. However, would doing so-by enacting an interest rate increase, for example-even decrease the prices of energy traded on the world market? In this Weekly Report, a time series model shows energy prices in Germany would sink by around four percent-even more strongly than the overall consumer price index at 0.2 percent- were the ECB to increase the interest rate. This is primarily due to the fact that such an increase would appreciate the euro, which would make dollar-traded oil imports cheaper. However, at the same time, an interest rate increase would derail industrial production and increase unemployment during an already slow economic recovery.
Keywords: E31; E52; Q43; 330; ECB monetary policy; energy prices; exchange rate channel